A study of the adequacy of Construction Industry Standard for manual calculation in Industrialised Building System (IBS) content - Mohamad Razi Ahmad Suhaimi (Tanjong Malim, 2019)
A study of the adequacy of Construction Industry Standard for manual calculation in Industrialised Building System (IBS) content by Mohamad Razi Ahmad Suhaimi